Uncontrolled hypertension in a rural population of Jammu and Kashmir - Priyadarshini Arambam; Rishabh Khashoo; Dhruv Tewari; Zubair Saleem; Sudhir Shekhawat; Upendra Kaul (Indian Heart Journal, 2022)
Aim: Evaluation of the status of uncontrolled hypertension in diagnosed hypertensives who had been advised drug treatment in the rural areas of 6 districts in Jammu & Kashmir (J&K) and also the risk factors associated with it. Methods: The study was a cross-sectional observational study conducted between August 2020 to July 2021 in the form of health camps in six government health centres in 6 different rural districts. The camps were focussed on patients with hypertension, diabetes with or without heart disease. The areas included Machil in Kupwara, Khan Sahib in Budgam, Rajpora and Hawal in Pulwama, Rainawari in the Srinagar, Banihal in Ramban, and Jagti in Jammu.Enrolled patients were examined for body weight, blood pressure (BP), random blood sugar and serum lipid profile. The definition of hypertension was as per the eighth Joint National Committee (JNC-8) guidelines. Results: A total of 600 patients (50.1% males) were evaluated. Of these 335 (55%) had history of being diagnosed hypertension and had been recommended drugs for BP control Male: Female ratio 1:0.8.211(63.5%) of these had un controlled blood pressures on measurement.Two or more drugs had been prescribed in 65 (30.8%) patients, 34 (16%) were taking only single drug and 112(53%) were not on any drug. Uncontrolled hypertension was seen more often in age group of 40–60 years (49%), subjects more than 60 years had it in 40%.The comparison of risk factors between patients with diagnosed hypertension with those without it revealed use of tobacco, consumption of salted tea, presence of diabetes, dyslipidaemia as significant factors for the presence of uncontrolled hypertension. Conclusion: Uncontrolled hypertension in known patients prescribed drugs is highly prevalent in the rural population of J&K. Steps to mitigate this problem are needed on top priority.